Sensitivity of GC‐EI/MS, GC‐EI/MS/MS, LC‐ESI/MS/MS, LC‐Ag+CIS/MS/MS, and GC‐ESI/MS/MS for analysis of anabolic steroids in doping control. Issue 11 (21st October 2015) - Cha, Eunju; Kim, Sohee; Kim, Ho Jun; Lee, Kang Mi; Kim, Ki Hun; Kwon, Oh‐Seung; Lee, Jaeick
Abstract : This study compared the sensitivity of various separation and ionization methods, including gas chromatography with an electron ionization source (GC‐EI), liquid chromatography with an electrospray ionization source (LC‐ESI), and liquid chromatography with a silver ion coordination ion spray source (LC‐Ag + CIS), coupled to a mass spectrometer (MS) for steroid analysis. Chromatographic conditions, mass spectrometric transitions, and ion source parameters were optimized. The majority of steroids in GC‐EI/MS/MS and LC‐Ag + CIS/MS/MS analysis showed higher sensitivities than those obtained with other analytical methods. The limits of detection (LODs) of 65 steroids by GC‐EI/MS/MS, 68 steroids by LC‐Ag + CIS/MS/MS, 56 steroids by GC‐EI/MS, 54 steroids by LC‐ESI/MS/MS, and 27 steroids by GC‐ESI/MS/MS were below cut‐off value of 2.0 ng/mL. LODs of steroids that formed protonated ions in LC‐ESI/MS/MS analysis were all lower than the cut‐off value. Several steroids such as unconjugated C3‐hydroxyl with C17‐hydroxyl structure showed higher sensitivities in GC‐EI/MS/MS analysis relative to those obtained using the LC‐based methods. The steroids containing 4, 9, 11‐triene structures showed relatively poor sensitivities in GC‐EI/MS and GC‐ESI/MS/MS analysis. The results of this study provide information that may be useful for selecting suitable analytical methods for confirmatory analysis of steroids. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This study compared the sensitivity of various methods, including gas chromatography with electron ionization source (GC‐EI), liquid chromatography with electrospray ionization source (LC‐ESI), and liquid chromatography with silver ion coordination ion spray source (LC‐Ag + CIS), coupled to a mass spectrometer (MS) for steroid analysis. The sensitivity for most steroids in GC‐EI/MS/MS and LC‐Ag + CIS/MS/MS were highest than other methods. The results of this study provide information that may be useful for selecting suitable analytical methods for confirmatory analysis of steroids.